2015
DOI: 10.1021/acs.est.5b03442
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Aromatic-Degrading Microbial Communities to Elevated Nitrate in Sediments

Abstract: A high number of aromatic compounds that have been released into aquatic ecosystems have accumulated in sediment because of their low solubility and high hydrophobicity, causing significant hazards to the environment and human health. Since nitrate is an essential nitrogen component and a more thermodynamically favorable electron acceptor for anaerobic respiration, nitrate-based bioremediation has been applied to aromatic-contaminated sediments. However, few studies have focused on the response of aromatic-deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…As one of the most common structural units of organic compounds in nature, the benzene ring and its derivatives are extensively used in industrial production, including daily supplies, agro-products, energy products, etc. Although some structural properties of these compounds make them recalcitrant to degradation, many aromatic-degrading microbes have been isolated ( Fuchs et al, 2011 ; Xu et al, 2015 ), with metabolic pathways and mechanisms reported for some ( Chauhan et al, 2000 ; Zhang et al, 2012 ; Shah et al, 2014 ; Gran-Scheuch et al, 2017 ), but not all ( Goncalves et al, 2006 ; Zhou et al, 2015 ). These works and hundreds of others have advanced our knowledge of aromatic compounds degradation.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most common structural units of organic compounds in nature, the benzene ring and its derivatives are extensively used in industrial production, including daily supplies, agro-products, energy products, etc. Although some structural properties of these compounds make them recalcitrant to degradation, many aromatic-degrading microbes have been isolated ( Fuchs et al, 2011 ; Xu et al, 2015 ), with metabolic pathways and mechanisms reported for some ( Chauhan et al, 2000 ; Zhang et al, 2012 ; Shah et al, 2014 ; Gran-Scheuch et al, 2017 ), but not all ( Goncalves et al, 2006 ; Zhou et al, 2015 ). These works and hundreds of others have advanced our knowledge of aromatic compounds degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows that high total PAHs (Σt-PAHs) were observed in the sediments that were subjected to frequent human activities, such as the water traffic artery (F1–F3), ship building and repairing industries (F4, R1–R5) and areas with riverside human communities (R1–R4, R8). As a result of their high hydrophobicity and persistence, PAHs entering the aquatic ecosystem tend to rapidly adsorb onto suspended particles and settle to the sediment where they become accumulated 54 . Similar to other studies 55 56 , we found the highly hydrophobic PAHs such as 4-ring and 5-ring PAHs dominated in sediments (31%–49% and 13%–36%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Significant (p < 0.05) increases were observed in bph encoding benzoate 4monooxygenase genes on day 90 involved in the degradation pathway of benzoyl-CoA, the most common intermediate in the anaerobic degradation of aromatic compounds. 37 The mhpA (229591541, 119899970, and 403195534) and phtA genes (118759687) with increasing signal intensity after SMFC employment, all were from bacteria Pseudomonas sp., Azoarcus sp., Escherichia sp., and Sphingomonas wittichii RW1 (Table S9). The mhpA and phtA genes from these organisms were involved in anaerobic degradation of toluene, ethylbenzene, and naphthalene.…”
Section: Effects Of Smfc Employment On Sediment Chemicalmentioning
confidence: 98%